2022
DOI: 10.3390/f13030399
|View full text |Cite
|
Sign up to set email alerts
|

Drought Effects on Morpho-Physiological and Biochemical Traits in Persian Oak and Black Poplar Seedlings

Abstract: In many arid and semi-arid regions, increasing water scarcity pushes woody species to their physiological limits, making strong drought resistance essential for adaptive forest management. Here, we examined morpho-physiological and biochemical drought responses of the forestry-relevant Persian oak (Quercus brantii Lindl.) and black poplar (Populus nigra L.). In a 120-day greenhouse pot experiment, seedlings were subjected to three watering regimes (FC100, FC60, and FC30, indicating percentages of field capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 68 publications
4
6
0
Order By: Relevance
“…Carr. and Prunus sargentii (Rehder) H. Ohba (1992) (Karimi et al 2022). Our study also showed that leaf water potential decreases with increased drought level and increased duration of drought.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Carr. and Prunus sargentii (Rehder) H. Ohba (1992) (Karimi et al 2022). Our study also showed that leaf water potential decreases with increased drought level and increased duration of drought.…”
Section: Discussionsupporting
confidence: 69%
“…Similarly, Tribulato et al (2019) reported that Polygala myrtifolia L. and Viburnum tinus L. had reduced biomass in both crops, but V. tinus had no differences among treatments with regard to root-to-shoot ratio at four different levels of drought treatments. In a study conducted by Karimi et al (2022), drought-stressed persian oak seedlings (20% field capacity) showed reduced plant height (-22% to -38%) and reduced diameter growth (-20% to -30%) compared with controls. The European black poplar (six genotypes) displayed decreased height (-32% to -88%) and diameter (-40% to -75%) when exposed to drought conditions (Viger et al 2016).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, greenhouse pot experiment under drought conditions with woody plant species such as pedunculate oak (Kebert et al, 2023), Persian oak (Quercus brantii Lindl.) and European black poplar (Populus nigra L.) also exhibited increased proline content (Karimi et al, 2022). Increased proline levels may be linked to improved plant tolerance to various abiotic stresses, including drought, because of the strong positive correlation between proline and antioxidant potential (FRAP and ABTS) that was observed in this study.…”
Section: Clone-specific Osmolyte (Glycine Betaine and Proline) Variab...supporting
confidence: 51%
“…A similar increasing trend of free proline was also reported in vitro in other plant species such as Prunus dulcis (Mill.) when it was treated with 7.5% PEG 6000 in MS medium (Karimi et al, 2022) as well as in Tacca leontopetaloides (Martin et al, 2021). Other plant species, including rice (Akte et al, 2011), almond (Akbarpour et al, 2017), mango (Pradhan et al, 2021), potato (Kumar et al, 2020), and Fragaria ananasa (Hussein et al, 2017), have also shown a droughtinduced increase in free proline levels.…”
Section: Clone-specific Osmolyte (Glycine Betaine and Proline) Variab...mentioning
confidence: 99%
See 1 more Smart Citation